-
If x = 6pq , then the value of x + 3p + x + 3q is p + q x − 3p x − 3q
-
- 6
- 8
- 2
- 3
Correct Option: C
x = | = | ||
p + q | p + q |
⇒ | = | ||
3p | p + q |
⇒ | = | ||
x − 3p | 2q − p − q |
(By componendo and dividendo)
⇒ | = | .....(i) | ||
x − 3p | q − p |
Again, x = | = | ||
p + q | p + q |
⇒ | = | ||
3q | p + q |
⇒ | = | ||
x − 3q | 2p − p − q |
(By componendo and dividendo)
⇒ | = | .....(ii) | ||
x − 3q | p − q |
∴ | + | = | + | ||||
x − 3p | x − 3q | q − p | p − q |
= | − | ||
q − p | q − p |
= | = | ||
q − p | q − p |
= | = 2 | |
q − p |